The Nordic Education Model in Context Historical Developments and Current Renegotiations - Tröhler, Daniel; Hörmann, Bernadette; Tveit, Sverre; Bostad, Inga (Political Economies of Capitalism, 1600-1850, 2023)
Tracing historical and cultural factors which gave rise to the Nordic Education Model, this volume explores why Northern European education policy has become an international benchmark for schooling. The text explains the historical connection between a Nordic ideal of democracy and schooling, and indicates how values of equality, welfare, justice, and individualism might be successfully integrated in national school systems and curricula around the world. The volume also highlights recent debates around the longevity of the Nordic model and explores the risks and challenges posed by international policy and assessment agendas. Exploring how Nordic education polices successfully merge social equity with academic excellence, the book combines cultural, historical, sociological and philosophical analysis with a deep exploration of curriculum and teaching. This book will be of great interest to researchers, scholars, and postgraduates working across the fields of curriculum, comparative education, cultural studies and history and philosophy of education and education policy.